Disposable iodophor cotton ball processing device - FU YIKAI (2024)
The utility model relates to the field of cotton ball processing devices, and discloses a disposable iodophor cotton ball processing device which comprises a box body, a first processing box is fixedly connected to one side of the upper surface in the box body, a driving device is arranged in the upper portion of the box body, and a placing mechanism is arranged on the lower portion of the driving device. Sealing plates are fixedly connected to the upper parts of the interiors of the first treatment box and the second treatment box, a filtering plate is fixedly connected to the upper part of the interior of the first treatment box, and a baffle is fixedly connected to the lower part of the interior of the first treatment box. According to the cotton raw material disinfection device, fan blades on a rotating shaft are rotated to stir disinfection liquid on a baffle plate in a first treatment box, so that cotton raw materials in a placing mechanism are disinfected in a washing manner, and then the cotton raw ma